What are British teachers expected to understand by the term 'Fundamental British Values' appearing in the Teaching Standards 2012? - Iqbal, Zafer (2017)
The post-9/11 era has resulted in the emergence of incompatible narratives in a propaganda war between Western governments, particularly the US and UK, and violent and non-violent global Islamic movements. One side seeks to maintain a hegemonic geopolitical order whilst the other seeks to replace it. This resulting conflict has indirectly and inadvertently impacted the British education system in a number of ways. This paper seeks to reveal the political, ideological and educational discourses influencing state ordained teaching imperatives and proscriptions relating to “fundamental British values” (FBV) originating in the Teaching Standards of 2012. A macro-analysis traces the educational policies reflecting liberalism, multiculturalism and securitisation aimed at assimilating ethnic minorities into a national framework of (neo-)liberal values. Muslims and Islam are increasingly problematised in their resistance to assimilation and potential as a fifth column. The emergence of FBV, underpinning a broader counter-terrorism security narrative as a new policy instrument to assimilate Muslims, is argued to be the latest twist in the war on terror. The selection of these values is dialectically shaped by corresponding Islamist values, which in turn underpin an effective Islamist narrative contesting Western hegemony. A meso-analysis considers the operationalisation of FBV into education policy through pre-determined consultations, Machiavellian political interventions and alliances with ideologically cognate think tanks and actors. A micro-analysis looks at how FBV related policy within a securitised context seeks to reshape teacher identity, recreating the teacher as a Foucauldian panopticon ideologue, objectifying Muslim students and pathologising their culture and values. The paper concludes this discourse is obscuring damaging assumptions in education, increasingly marginalising critical thinking, statutorily forcing teachers to indoctrinate students with liberal values and police their thoughts, resulting in increasing fear, suspicion and doubt across the schooling system. Critical discourse analysis and untellability theory are employed to explain how the current discourse has been shaped and privileged by the ideology of state whilst competing values are marginalised, deprivileged and “othered”.